Changes in the amount of Glutathione in Arsenic Loaded Tissue reflecting the effectiveness of arsenic removal from Isolated Liver Tissues in Experimental Rat - Iqbal Ira, Andalib Mustafa; Misbahuddin, Mir; Khan, Asma; Yusuf, Md Abdullah; Saha, Shaymol Kumar; Jahan, Tuhin (Journal of National Institute of Neurosciences Bangladesh, 2022)
Background: Removal of glutathione is essential during metabolism of the body. Objective: The purpose of the present study was to see the ability of spirulina, Allium sativum (Garlic), Ipomoea aquatic (Water Spinach) for the prevention of depletion of intracellular glutathione in arsenic loaded isolated liver tissues of experimental rat. Methodology: This animal study was carried out on isolated liver tissues of Long Evans Norwegian adult healthy male rats weighing 160 to 200 g. The rats were 3 to 6 months of age obtained from animal house of Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh from 2004 to 2005. Measurements and all tasks were performed in a very careful manner. Atomic Absorption Spectrophotometer with Hydride Generator was used to measure the arsenic level. Results: The concentration of glutathione was 434.02 μg/g of protein. With 2.5 μg/ml arsenic trioxide, the amount of gluthathione was depleted to 344.33 μg/g of protein. There was 79.26% of glutathione in that tissues comparing with control. The amount of glutathione was 20.74% less than control. About 2.5 μg/ml arsenic trioxide added tissues were subsequently incubated with SI extract of spirulina and the amount of glutathione was 351.66 μg/g of protein. There was 80.87% glutathione when compared with control and there was 19.13% less than control. There was 4.84% less of amount of glutathione. Both G1 and G2 (hexane and methanol) extract of garlic added tissues showed amount of glutathione 346.85 peg of protein. After comparing with control there was 82.25% glutathione. So there was 17.75% depletion of glutathione. Conclusion: In conclusion ability of extract of spirulina, Allium sativum (Garlic), Ipomoea aquatic (Water Spinach) have the role in the prevention of depletion of intracellular glutathione in arsenic loaded isolated liver tissues of experimental rat. Journal of National Institute of Neurosciences Bangladesh, January 2022; 8(1):46-51